Structural trapping capacity of oil-wet caprock as a function of pressure, temperature and salinity. (July 2016) - Arif, Muhammad; Barifcani, Ahmed; Lebedev, Maxim; Iglauer, Stefan
Graphical abstract: Highlights: Effect of pressure and temperature on wettability of CO2 -brine-mineral system of different original wettability states. Effect of salinity on wettability of CO2 -brine-mineral systems. Wettability regime mapping. Implications of the measured data for structural trapping capacities. Abstract: Wettability is a major parameter which significantly influences structural trapping capacities in CO2 geo-sequestration. In this context, the original wettability state of a caprock is of key importance, however, less attention has been given towards this aspect in the past. We thus evaluated the impact of caprock oil-wettability on storage potential; we used five mica substrates as representatives of caprock and modified their initial wettability to obtain different oil-wetness (0–118° water contact angle at ambient conditions), so that we were able to conduct a systematic study. Advancing and receding contact angles (θa and θr ) were measured on all surfaces for wide ranges of pressure (0.1 MPa–20 MPa), temperature (308 K, 323 K and 343 K) and salinity (0 wt%–20 wt% NaCl). The results indicate that advancing and receding contact angles increase with pressure (when pressure increased from 0.1 MPa to 20 MPa at 343 K, θa increased from 0° to 67° for water-wet substrate and from 73° to 156° for oil-wet substrate), and salinity but decrease with temperature. Finally we predict CO2 column heights, which can be permanently stored beneath oil-wet caprocks. Clearly, the structural trapping capacity is significantly reduced in case of oil-wet caprock (when compared to water-wet caprock). We conclude that it is essential to evaluate CO2 -wettability of caprocks to determine safe limits of operation for containment security.